Under Solomon’s Tutelage: The Education of Desire in the Homilies on the Song of Songs - Laird, Martin (Modern theology, 2002)
This essay examines how Gregory of Nyssa sees the Solomonic books of Scripture (Proverbs, Ecclesiastes, Song of Songs) train desire to long for God. The philosophical exercises contained in Proverbs and Ecclesiastes prepare the soul for the supreme training contained in the Song of Songs. The purpose of the Song of Songs is to lead the soul to union with God. The Trinitarian strategy of the philosophy contained in the Song of Songs exposes the soul to paradox and oxymoron, through which the soul is schooled to release its noetic-erotic grasp of concepts and is thus led to apophatic union with God.